Whale optimization algorithm based rigid and non-rigid registration - Roy, Abhisek; Kanti Roy, Pranab; Mitra, Anirban; Roy Choudhury, Sraddha; Chakraborty, Sayan (Edelweiss Applied Science and Technology, 2024)
Image registration has become one of the most widely used transformation techniques in satellite and medical imaging nowadays is image registration. Mapping of two or more than two images are known as registration of images. Multimodal images are those that are processed using the same registration model but were taken with different devices. In the current work, we introduce a multimodal image registration framework on which we have applied two meta-heuristic algorithms: the Whale Optimization Algorithm (WOA) and Particle Swarm Optimization (PSO), to reduce processing time and enhance the performance of both rigid and non-rigid multimodal registration frameworks. The outcomes of WOA and PSO based framework has been compared with each other with respect to both rigid and non-rigid frameworks.